Analysis of Design Rainfall Depth in Sponge City Construction — a Case Study of Hefei, China. Issue 4 (April 2020) - Song, Xinwei; Tu, Youxiao; Chai, Luxiu
Abstract: The design rainfall depth is an important parameter in the construction of sponge cities. Based on the analysis of 39 year daily precipitation data in Hefei city, this paper concludes that the inter-annual and intra-annual distribution of precipitation in Hefei is uneven. Based on the comparison and analysis of volume capture ratio of annual rainfall calculation method and rainfall percentage control calculation method for design rainfall depth, it is proposed that the designed rainfall in Hefei should not be too high, and it provides suggestions for the construction of the sponge city in Hefei.